Remineralization potential and caries preventive efficacy of CPP-ACP/Xylitol/Ozone/Bioactive glass and topical fluoride combined therapy versus fluoride mono-therapy – a systematic review and meta-analysis. (18th August 2021) - Sharda, Shweta; Gupta, Arpit; Goyal, Ashima; Gauba, Krishan
Abstract: Objective: To compare the remineralization potential and caries preventive efficacy of CPP-ACP/bioactive glass/xylitol/ozone and topical fluoride (TF) combined therapy versus TF mono-therapy. Material and methods: Embase, PubMed, Scopus, Web of Science and Cochrane databases were searched. 4457 records were screened and 26 trials were included. Data from 16 trials was pooled using Review Manager 5.4. Level of significance was p  < .05. The certainty of the evidence was evaluated using GRADE. Results: Pooled analysis of two trials for white spot lesions (WSLs) regression (SMD −0.6, 95% CI: [−1.07 to −0.14], p  = .01) and three trials for post-intervention DIAGNOdent values (SMD −1.24, 95% CI: [−1.96 to −0.52], p  = .0007) significantly favoured CPP-ACP-TF combined therapy over TF mono-therapy. The sub-group analysis for caries increment (SMD −0.14, 95% CI: [−0.21 to −0.07], p  < .0001) and the post intervention S mutans count (SMD −0.42, 95% CI: [−0.62 to −0.23], p  < .0001) significantly favours 'xylitol-TF' and 'CPP-ACP-TF' combined therapy respectively. The high/unclear risk of bias, imprecision and indirectness of the included trials presented a low certainty of evidence. Conclusion: CPP-ACP-TF exhibits superiority over TF monotherapy in remineralizing existing lesions and demonstrates better antibacterial effect, whereas it is not more effective for preventing caries incidence. However, Xylitol exerts an added benefit over fluoride alone in preventing caries increment. The low-certainty evidence highlights the need for more good quality trials.